Para além de uma Vocação: Sentido do Trabalho para os Professores da Unidade Escolar Municipal Conveniada Belo Campo (Management and Connections Journal, 2022)
The human perception of work has undergone changes: from punishment to essential to life. Thus, the study of the meaning of work became important to understand the relationship between subject and organization. Therefore, this article aims to analyze the meaning of work for teachers at the Municipal School Unit Conveniada Belo Campo, in Belo Campo, Southwestern of Bahia. This research is empirical in nature, descriptive-exploratory and the research strategy was the case study. Adopting a probabilistic sampling, 37 teachers answered a structured questionnaire and, due to accessibility, eight teachers were interviewed. The results revealed a feeling of devaluation, triggered mainly by low salaries and lack of recognition by students and the government, in addition to tiredness caused by work overload. However, teachers are satisfied with their work and are proud of what they do.
Keywords: Pleasure; Suffering; Teaching Work